Method for preparing porous ceramic by polymer derived ceramic route

Through polymer-derived ceramic routes and phase conversion molding technology, the problems of low porosity and complex preparation process of ceramic ultrafiltration membranes are solved, and efficient preparation and performance improvement of hollow fiber ceramic ultrafiltration membranes are achieved.

CN119430986APending Publication Date: 2025-02-14JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411603473.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing ceramic ultrafiltration membrane has low porosity, poor permeability and complex preparation process, making it difficult to directly prepare hollow fiber ceramic ultrafiltration membranes.

Method used

Hollow fiber ceramic ultrafiltration membranes are prepared by cross-linking of polymer ceramic precursors, preparation of cast film liquid and high-temperature sintering.

Benefits of technology

The preparation process of ceramic ultrafiltration membrane is simplified, the porosity and permeability of the membrane are improved, and the high purity and composition controllability of ceramic materials are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430986A_ABST
    Figure CN119430986A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing porous ceramic through a polymer derived ceramic route, and belongs to the technical field of ceramic preparation, and the method comprises the following steps: cross-linking of a polymer ceramic precursor: carrying out multi-stage heat treatment on the polymer ceramic precursor for cross-linking; preparation of membrane casting slurry: preparing the polymer ceramic precursor into the membrane casting slurry; phase inversion molding: drying the membrane casting slurry to obtain a hollow fiber ceramic membrane precursor; and sintering at high temperature to obtain the porous ceramic. According to the preparation method of the porous ceramic, a polymer derived ceramic technology and phase inversion are combined for preparation, the forming of a fiber membrane can be easily realized without other extra conditions only by preparing a membrane casting solution and regulating spinning process parameters, and the membrane casting solution prepared from cross-linked polymethylsilsesquioxane or MK is fast in curing and forming in the phase inversion process, so that the preparation method is simple, and the preparation cost is low. The preparation process of the hollow fiber ceramic ultrafiltration membrane is simpler, more convenient and more efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic preparation, and in particular to a method for preparing porous ceramics through a polymer-derived ceramic route. Background Art

[0002] Ceramic membranes have been widely used in water treatment, food industry, energy engineering, biopharmaceutical engineering and other fields due to their excellent separation performance and reliable chemical, mechanical and thermal stability. Ceramic ultrafiltration membranes with pore sizes of 2nm to 100nm are widely used in oily wastewater, heavy metal ion wastewater, papermaking wastewater, etc. The impurities and pollutants in the wastewater are selectively screened by the pore size of the ultrafiltration membrane, achieving wastewater purification and resource recycling.

[0003] Common ceramic membranes are usually composed of a support layer with a certain mechanical strength, an intermediate transition layer and a functional separation layer, presenting an asymmetric structure. In the process of preparing ceramic membranes, it is necessary to prepare the support layer, the intermediate layer and the separation layer separately, and each layer needs to be sintered at high temperature. Usually, commercial ceramic microfiltration membranes have at least 3 layers, while ceramic ultrafiltration membranes have as many as 4 to 5 layers, and the overall membrane layer is thicker, the porosity is low (<35%), and the membrane permeation resistance is larger, which leads to the complexity of the entire preparation process of ceramic ultrafiltration membranes, the longer preparation cycle and the poor permeability performance. Problems in any step during the preparation of ceramic membranes will cause defects in the prepared ceramic ultrafiltration membranes, resulting in a decrease in the performance and yield of the membranes.

[0004] Compared with the multiple preparation and multiple sintering preparation processes of traditional ceramic membranes, the technology of phase transformation one-step molding combined with one-time high-temperature sintering is more advantageous. The preparation of hollow fiber ceramic membranes with self-supporting asymmetric structures by phase transformation one-step molding and one-time high-temperature sintering effectively shortens the cost and cycle of ceramic membrane preparation. Hollow fiber ceramic membranes have the advantages of thin membrane layer, excellent permeation flux, high packing density and flexible use, and the microstructure and performance are highly controllable. At present, phase transformation is mainly used for the preparation of hollow fiber ceramic microfiltration membranes. If you want to directly prepare hollow fiber ceramic ultrafiltration membranes by phase transformation, you need ceramic powders with smaller particle sizes. However, the reduction of ceramic powder particle size will be accompanied by a sharp increase in specific surface area, resulting in excessive viscosity of the casting liquid and agglomeration of ceramic particles, which will make the casting liquid less stable and bring difficulties to dry / wet spinning. Another method for preparing hollow fiber ceramic ultrafiltration membrane is to coat a membrane layer on the hollow fiber ceramic microfiltration membrane support. Common methods include the sol-gel method, but overall the membrane preparation cost is high, the preparation process is complicated, and the membrane layer is prone to cracking after drying, and the yield of the membrane product and the performance of the membrane cannot be guaranteed.

[0005] In recent years, the preparation of porous ceramics by polymer-derived ceramics (PDCs) has attracted widespread attention due to its advantages such as simple process, controllable micro-nanoscale fine structure and low-temperature preparation. The PDCs method can prepare a variety of ceramic materials, such as oxides, silicates, nitrides and carbides. If hollow ceramic ultrafiltration membranes can be prepared by the polymer-derived ceramics route and used for oily wastewater and heavy metal ion wastewater, it will be expected to solve the problems of low porosity, poor permeability and complex preparation process of existing ceramic ultrafiltration membranes. At present, there is no literature report on the preparation of hollow fiber ceramic ultrafiltration membranes by the polymer-derived ceramics route. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing porous ceramics by a polymer-derived ceramic route to solve the problem raised in the background technology, and to prepare hollow fiber ceramic ultrafiltration membranes by a polymer-derived ceramic route.

[0007] In order to solve the above technical problems, the technical solution of the present invention is:

[0008] A method for preparing porous ceramics by a polymer-derived ceramic route, the method comprising the following steps:

[0009] Crosslinking of polymer ceramic precursors:

[0010] The polymer ceramic precursor is cross-linked through multi-stage heat treatment. At 20°C, the temperature is raised to 80°C at a rate of 1°C / min and kept for 2h, then raised to 140°C at a rate of 1°C / min and kept for 2h, and finally raised to 200°C at a rate of 1°C / min and kept for 2h before natural cooling.

[0011] Preparation of casting slurry:

[0012] When the polymer ceramic precursor used is polymethylsilsesquioxane, polyethersulfone (PES) is added to the solvent N-methylpyrrolidone (NMP), and stirred for 3 hours with a stirrer equipped with a polytetrafluoroethylene stirring paddle to obtain a polymer solution, and pre-crosslinked polymethylsilsesquioxane and inert filler α-Al2O3 are first added to the polymer solution in small amounts and multiple times and stirred for 2 hours, and then polyvinylpyrrolidone (PVP) is added and stirred for 1 hour, and the obtained casting solution is vacuum degassed; wherein, when the synthesized ceramic ultrafiltration membrane is mullite, α-Al2O3 needs to be added to the casting solution, but not in other cases;

[0013] When the polymer ceramic precursor used is MK, MK is dissolved in a mixed solvent of DMF and anhydrous ethanol and stirred thoroughly, and then a polymer binder PMMA is added thereto and stirred thoroughly to obtain a casting solution, and vacuum degassing is performed. When the chemical composition of the synthesized ceramic ultrafiltration membrane is mullite, an inert filler α-Al2O3 needs to be added to the casting solution, and no inert filler is added in other cases;

[0014] Phase inversion molding:

[0015] When the polymer ceramic precursor used is polymethylsilsesquioxane, the core liquid is tap water, the external coagulation bath is tap water, the air distance is 2 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after a certain air distance, and after soaking in the external coagulation bath for 24 hours, the solvent and the non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying; when the polymer ceramic precursor used is MK, the external coagulation bath is anhydrous ethanol, the air distance is 6 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after a certain air distance, and after soaking in the external coagulation bath for 24 hours, the solvent and the non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying;

[0016] High temperature sintering:

[0017] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, a certain length of the hollow fiber ceramic membrane precursor is cut and loaded into the alumina tubular membrane tube, and the temperature is first raised from room temperature to 950°C at a rate of 2°C / min and kept for 2 hours in an air atmosphere, and then the temperature is raised to 1400°C-1600°C at a rate of 5°C / min and kept for 2 hours;

[0018] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiO2, the temperature is first raised from room temperature to 800°C at a rate of 2°C / min and kept for 2 hours in an air atmosphere, and then the temperature is raised to 1000°C-1200°C at a rate of 5°C / min and kept for 2 hours;

[0019] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiOC, the temperature is raised to 800°C at a rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 hours, then the temperature is raised to 1000°C at a rate of 4°C / min and oxygen is introduced and kept warm for 5 hours.

[0020] Preferably, when the polymer ceramic precursor used is polymethylsilsesquioxane, the chemical formula of the hollow fiber ceramic ultrafiltration membrane is mullite, wherein 1:4≤PES:NMP≤1:6, 14wt%≤polymethylsilsesquioxane≤25wt%, 26wt%≤α-Al2O3≤35wt%, 40wt%≤NMP≤50wt%.

[0021] Preferably, when the polymer ceramic precursor used is polymethylsilsesquioxane, when the chemical formula of the hollow fiber ceramic ultrafiltration membrane is mullite, the weight percentage of the casting solution is: 40.68wt% NMP, 9.18wt% PES, 29.08wt% α-Al2O3, 15.81wt% polymethylsilsesquioxane, wherein the particle size of the polymethylsilsesquioxane is ≤5μm, D 50 =2μm.

[0022] Preferably, when the polymer ceramic precursor MK is used, the solvent is DMF and anhydrous ethanol, the mass ratio of DMF to anhydrous ethanol is 3:2, and 10wt%≤MK≤25wt%.

[0023] Preferably, when the polymer ceramic precursor MK is used, the weight percentages of the casting solution include: 16 wt % of anhydrous ethanol, 24 wt % of DMF, 8 wt % of PMMA, 34 wt % of α-Al 2 O 3 and 16 wt % of MK.

[0024] The above technical solution has the following beneficial effects:

[0025] 1. The preparation is combined with polymer-derived ceramic technology and phase inversion. Only the casting solution is prepared and the spinning process parameters are adjusted. No other additional conditions are required to easily form the fiber membrane. The casting solution prepared with cross-linked polymethylsilsesquioxane or MK solidifies and forms quickly during the phase inversion process, making the preparation process of hollow fiber ceramic ultrafiltration membrane simpler and more efficient.

[0026] 2. Polymer-derived ceramic technology can obtain the desired ceramic composition by synthesizing precursor polymers with specific chemical structures. Since the source of ceramics is polymers, this method can achieve high purity and composition controllability of ceramic materials. Oxide ceramic films and non-oxide ceramic films can be prepared by controlling the precursor composition. These oxide and non-oxide ceramic films require extremely high firing temperatures and complex processing processes using traditional powder molding;

[0027] 3. The porosity of ceramic ultrafiltration membranes prepared from nano-ceramic powders is not high, and the structure of the fired pores is uneven and difficult to control. Polymer-derived ceramic technology can use the gases or other substances produced during the decomposition of polymers to form a uniform nanoscale pore structure, which makes the hollow fiber ceramic membrane have uniformly distributed nanoscale pores, high porosity, and high permeability flux. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention provides an XRD spectrum of porous ceramics prepared by a polymer-derived ceramic route. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The purpose of the present invention is to provide two polymer ceramic precursor materials with excellent performance and low cost, overcome the technical problem of the difficulty in matching the PDCs route with the phase inversion technology, simplify the ceramic ultrafiltration membrane preparation process, and improve the performance of the ceramic ultrafiltration membrane. The pore size and porosity of the porous material prepared by PDCs can be regulated by adjusting the composition and process parameters of the precursor. As an alternative to the powder route commonly used in the field of electrostatic chucks to prepare ceramics, PDCs is combined with the phase inversion molding technology, and is expected to directly prepare a hollow fiber ceramic ultrafiltration membrane with high porosity and uniformly distributed nano-scale pores. This method effectively simplifies the membrane preparation process and reduces the preparation cost;

[0031] Currently available organosilicon polymer precursors include polysiloxane, polysilane, polycarbosilane, polysilazane, polyborosilazane, etc., which provide a wide range of choices for the application of porous ceramics. According to the type of polymer precursor and the heat treatment conditions, amorphous or crystalline ceramic membranes can be prepared, and the pore size of the ceramic membrane can range from nanometers to micrometers. The challenge of combining phase inversion technology with the PDCs route to prepare hollow fiber ceramic membranes is to determine a suitable solvent / non-solvent system for highly hydrophobic ceramic precursors. Many organosilicon precursors cannot be effectively matched with phase inversion technology due to their own chemical stability. Solvents traditionally used for phase inversion preparation of hollow fiber ceramic membranes, such as NMP, DMF, DMSO and DMAC, cannot effectively dissolve polymer ceramic precursors.

[0032] In order to solve the above technical problems, the scheme of the present application adopts novel polymer precursors as polymethylsilsesquioxane and polymethylhydrogensiloxane (MK), and the molding method adopted is dry / wet spinning-phase inversion technology. The polymer ceramic precursor and molding method provided by the present invention can effectively prepare hollow fiber ceramic ultrafiltration membranes with high flux, high porosity (>40%), narrow pore size distribution, uniform pore structure, high mechanical strength and toughness, and the microstructure of the membrane is highly controllable. High-performance ceramic ultrafiltration membranes can be prepared for specific applications, which effectively solves the technical problems of low porosity and permeation flux, complex preparation process, etc. of hollow fiber ceramic ultrafiltration membranes prepared by using ceramic powder as raw materials;

[0033] The present invention provides two polymer ceramic precursors with excellent performance, polymethylsilsesquioxane or polymethylhydrogensiloxane (, the molecular formulas of polymethylsilsesquioxane and polymethylhydrogensiloxane are [Si(CH3)2O]n and [CH3)(H)SiO]n, respectively, and the ceramic yields of the two precursors are 72% and 83% respectively;

[0034] A method for preparing porous ceramics by a polymer-derived ceramic route comprises the following steps:

[0035] Crosslinking of polymer ceramic precursors:

[0036] The polymer ceramic precursor is cross-linked through multi-stage heat treatment. The polymer ceramic precursor is cross-linked through multi-stage heat treatment in the following manner: at 20°C, the temperature is raised to 80°C at a rate of 1°C / min and kept for 2h, then the temperature is raised to 140°C at a rate of 1°C / min and kept for 2h, and finally the temperature is raised to 200°C at a rate of 1°C / min and kept for 2h and then naturally cooled. The temperature is gradually raised to ensure the full progress of the cross-linking reaction and the stability of the material structure;

[0037] Preparation of casting slurry:

[0038] When the polymer ceramic precursor used is polymethylsilsesquioxane, polyethersulfone (PES) is added to the solvent N-methylpyrrolidone (NMP), and stirred for 3 hours with a stirrer equipped with a polytetrafluoroethylene stirring paddle to obtain a polymer solution, and the pre-crosslinked polymethylsilsesquioxane and inert filler α-Al2O3 completed in the previous step are first added to the polymer solution, and added in small amounts and multiple times and stirred for 2 hours, and then polyvinylpyrrolidone (PVP) is added and stirred for 1 hour, and the obtained casting liquid is vacuum degassed; wherein, when the synthesized ceramic ultrafiltration membrane is mullite, α-Al2O3 needs to be added to the casting liquid, and when the synthesized ceramic ultrafiltration membrane is SiO2 or SiOC, α-Al2O3 is not added;

[0039] Among them, when the polymer ceramic precursor used is polymethylsilsesquioxane, and the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, α-Al2O3 needs to be added when preparing the casting solution, and the mass ratio of PES to NMP at this time satisfies: 1:4≤PES:NMP≤1:6, preferably PES:NMP=1:5, the weight percentage of polymethylsilsesquioxane satisfies: 14wt%≤polymethylsilsesquioxane≤25wt%, the weight percentage of the added α-Al2O3 satisfies: 26wt%≤α-Al2O3≤35wt%, and the weight percentage of the added NMP satisfies, 40wt%≤NMP≤50wt%;

[0040] Specifically, when the polymer ceramic precursor used is polymethylsilsesquioxane, and the chemical formula of the hollow fiber ceramic ultrafiltration membrane is mullite, the preferred weight percentage of the above-mentioned casting solution is: 41wt% NMP, 8.2wt% PES, 29wt% α-Al2O3, 16wt% polymethylsilsesquioxane, wherein the size of the polymethylsilsesquioxane satisfies: particle size ≤5μm, D 50 =2μm;

[0041] In other embodiments of this embodiment, when the polymer ceramic precursor used is polymethylsilsesquioxane, and the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, α-Al2O3 needs to be added when preparing the casting solution, and the mass ratio of PES to NMP at this time satisfies: PES:NMP=1:4, the weight percentage of polymethylsilsesquioxane is 14wt%, the weight percentage of α-Al2O3 added is 26wt%, and the weight percentage of NMP added is 40wt%;

[0042] In other embodiments of this embodiment, when the polymer ceramic precursor used is polymethylsilsesquioxane, and the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, α-Al2O3 needs to be added when preparing the casting solution, and the mass ratio of PES to NMP is 1:6, the weight percentage of polymethylsilsesquioxane is 25wt%, the weight percentage of the added α-Al2O3 is 35wt%, and the weight percentage of the added NMP is 50wt%;

[0043] When the polymer ceramic precursor used is polymethylhydrogensiloxane (MK), MK is dissolved in a mixed solvent of DMF (dimethylformamide) and anhydrous ethanol and stirred thoroughly, and then a polymer binder PMMA (polymethyl methacrylate) is added thereto and stirred thoroughly to obtain a casting solution, and vacuum degassing treatment is performed. When the chemical composition of the synthesized ceramic ultrafiltration membrane is mullite, an inert filler α-Al2O3 needs to be added to the casting solution. When the synthesized ceramic ultrafiltration membrane is SiO2 or SiOC, α-Al2O3 is not added.

[0044] When the polymer ceramic precursor is MK, the solvent is DMF and anhydrous ethanol, wherein the mass ratio of DMF to anhydrous ethanol is 3:2, and the weight percentage of MK satisfies: 10wt%≤MK≤25wt%;

[0045] When the polymer ceramic precursor MK is used, the weight percentage of the casting solution is specifically: 16wt% of anhydrous ethanol, 24wt% of DMF, 8wt% of PMMA, 34wt% of α-Al2O3 and 16wt% of MK;

[0046] In other implementations of this embodiment, when the polymer ceramic precursor is MK, the solvent is DMF and anhydrous ethanol, wherein the mass ratio of DMF to anhydrous ethanol is 3:2, and the weight percentage of MK is 10wt% or 25wt%;

[0047] Phase inversion molding:

[0048] When the polymer ceramic precursor used is polymethylsilsesquioxane, the core liquid is tap water, the external coagulation bath is tap water, the air distance is 2 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after a period of air distance. After soaking in the external coagulation bath for 24 hours, the solvent and non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying;

[0049] When the polymer ceramic precursor used is MK, the external coagulation bath is anhydrous ethanol, the air distance is 6 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after passing through a certain air distance. After soaking in the external coagulation bath for 24 hours, the solvent and non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying;

[0050] High temperature sintering:

[0051] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, a certain length of the hollow fiber ceramic membrane precursor is cut and loaded into the alumina tubular membrane tube, and the temperature is first raised from room temperature to 950°C at a rate of 2°C / min and kept warm for 2 hours in an air atmosphere, and then the temperature is raised from 950°C to 1400°C at a rate of 5°C / min and kept warm for 2 hours to complete the high-temperature sintering of the hollow fiber ceramic ultrafiltration membrane. In other implementations of this embodiment, after the temperature is raised from room temperature to 950°C, the temperature is then raised from 950°C to 1600°C at a rate of 5°C / min and kept warm for 2 hours to complete the high-temperature sintering of the hollow fiber ceramic ultrafiltration membrane;

[0052] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiO2, the temperature is first raised from room temperature to 800°C at a rate of 2°C / min for 2 hours in an air atmosphere, and then the temperature is raised from 800°C to 1000°C at a rate of 5°C / min for 2 hours to complete the high-temperature sintering of the hollow fiber ceramic ultrafiltration membrane. In other implementations of this embodiment, after the temperature is raised to 800°C at a rate of 2°C / min, the temperature is raised from 800°C to 1200°C at a rate of 5°C / min for 2 hours to complete the high-temperature sintering of the hollow fiber ceramic ultrafiltration membrane.

[0053] When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiOC, the temperature is raised from room temperature to 800°C at a rate of 2°C / min under a nitrogen atmosphere for 2 hours, and then the temperature is raised from 800°C to 1000°C at a rate of 4°C / min, and oxygen is introduced for 5 hours to complete the high-temperature sintering of the hollow fiber ceramic ultrafiltration membrane;

[0054] refer to Figure 1 , which is the XRD pattern of porous ceramics prepared by the polymer-derived ceramic route of this application. The XRD pattern of porous ceramics usually contains multiple peaks, which correspond to different grains in the ceramic material. XRD (X-ray diffraction) is a technology used to analyze the crystal structure of a material. It determines the crystal structure and grain size of a material by measuring the diffraction pattern after X-rays pass through the material.

[0055] The porous ceramics are prepared by the above technical solution. Compared with the methods of the prior art, the method for preparing the porous ceramics of the present application has the following beneficial advantages:

[0056] 1. The preparation is combined with polymer-derived ceramic technology and phase inversion. Only the casting solution is prepared and the spinning process parameters are adjusted. No other additional conditions are required to easily form the fiber membrane. The casting solution prepared with cross-linked polymethylsilsesquioxane or MK solidifies and forms quickly during the phase inversion process, making the preparation process of hollow fiber ceramic ultrafiltration membrane simpler and more efficient.

[0057] 2. Polymer-derived ceramic technology can obtain the desired ceramic composition by synthesizing precursor polymers with specific chemical structures. Since the source of ceramics is polymers, this method can achieve high purity and composition controllability of ceramic materials. Oxide ceramic films and non-oxide ceramic films can be prepared by controlling the precursor composition. These oxide and non-oxide ceramic films require extremely high firing temperatures and complex processing processes using traditional powder molding;

[0058] 3. The porosity of ceramic ultrafiltration membranes prepared from nano-ceramic powders is not high, and the structure of the fired pores is uneven and difficult to control. Polymer-derived ceramic technology can use the gases or other substances produced during the decomposition of polymers to form a uniform nanoscale pore structure, which makes the hollow fiber ceramic membrane have uniformly distributed nanoscale pores, high porosity, and high permeability flux.

[0059] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A method for preparing porous ceramics via a polymer-derived ceramic route, characterized in that: The method comprises the following steps: Crosslinking of polymer ceramic precursors: The polymer ceramic precursor is cross-linked through multi-stage heat treatment. At 20°C, the temperature is raised to 80°C at a rate of 1°C / min and kept for 2h, then raised to 140°C at a rate of 1°C / min and kept for 2h, and finally raised to 200°C at a rate of 1°C / min and kept for 2h before natural cooling. Preparation of casting slurry: When the polymer ceramic precursor used is polymethylsilsesquioxane, polyethersulfone (PES) is added to the solvent N-methylpyrrolidone (NMP), and stirred for 3 hours with a stirrer equipped with a polytetrafluoroethylene stirring paddle to obtain a polymer solution, and pre-crosslinked polymethylsilsesquioxane and inert filler α-Al2O3 are first added to the polymer solution in small amounts and multiple times and stirred for 2 hours, and then polyvinylpyrrolidone (PVP) is added and stirred for 1 hour, and the obtained casting solution is vacuum degassed; wherein, when the synthesized ceramic ultrafiltration membrane is mullite, α-Al2O3 needs to be added to the casting solution, but not in other cases; When the polymer ceramic precursor used is MK, MK is dissolved in a mixed solvent of DMF and anhydrous ethanol and stirred thoroughly, and then a polymer binder PMMA is added thereto and stirred thoroughly to obtain a casting solution, and vacuum degassing is performed. When the chemical composition of the synthesized ceramic ultrafiltration membrane is mullite, an inert filler α-Al2O3 needs to be added to the casting solution, and no inert filler is added in other cases; Phase inversion molding: When the polymer ceramic precursor used is polymethylsilsesquioxane, the core liquid is tap water, the external coagulation bath is tap water, the air distance is 2 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after a certain air distance, and after soaking in the external coagulation bath for 24 hours, the solvent and the non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying; when the polymer ceramic precursor used is MK, the external coagulation bath is anhydrous ethanol, the air distance is 6 cm, the core liquid flow rate is 48 ml / min, the nitrogen pressure is 1 bar, the casting liquid is squeezed out from one end of the spinning needle of the spinning device, and enters the external coagulation bath for solidification after a certain air distance, and after soaking in the external coagulation bath for 24 hours, the solvent and the non-solvent are fully exchanged, and the hollow fiber ceramic membrane precursor is obtained after drying; High temperature sintering: When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is mullite, a certain length of the hollow fiber ceramic membrane precursor is cut and loaded into the alumina tubular membrane tube, and the temperature is first raised from room temperature to 950°C at a rate of 2°C / min and kept for 2 hours in an air atmosphere, and then the temperature is raised to 1400°C-1600°C at a rate of 5°C / min and kept for 2 hours; When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiO2, the temperature is first raised from room temperature to 800°C at a rate of 2°C / min and kept for 2 hours in an air atmosphere, and then the temperature is raised to 1000°C-1200°C at a rate of 5°C / min and kept for 2 hours; When the chemical formula of the hollow fiber ceramic ultrafiltration membrane to be prepared is SiOC, the temperature is raised to 800°C at a rate of 2°C / min in a nitrogen atmosphere and kept warm for 2 hours, then the temperature is raised to 1000°C at a rate of 4°C / min and oxygen is introduced and kept warm for 5 hours.

2. The method for preparing porous ceramics by a polymer-derived ceramic route according to claim 1, characterized in that: When the polymer ceramic precursor used is polymethylsilsesquioxane, the chemical formula of the hollow fiber ceramic ultrafiltration membrane is mullite, wherein 1:4≤PES:NMP≤1:6, 14wt%≤polymethylsilsesquioxane≤25wt%, 26wt%≤α-Al2O3≤35wt%, and 40wt%≤NMP≤50wt%.

3. The method for preparing porous ceramics by a polymer-derived ceramic route according to claim 2, characterized in that: When the polymer ceramic precursor used is polymethylsilsesquioxane, and the chemical formula of the hollow fiber ceramic ultrafiltration membrane is mullite, the weight percentage of the casting solution is: 40.68wt% NMP, 9.18wt% PES, 29.08wt% α-Al2O3, 15.81wt% polymethylsilsesquioxane, wherein the particle size of the polymethylsilsesquioxane is ≤5μm, D 50 =2μm.

4. The method for preparing porous ceramics by a polymer-derived ceramic route according to claim 1, characterized in that: When the polymer ceramic precursor MK is used, the solvent is DMF and anhydrous ethanol, the mass ratio of DMF to anhydrous ethanol is 3:2, and 10wt%≤MK≤25wt%.

5. The method for preparing porous ceramics by a polymer-derived ceramic route according to claim 4, characterized in that: When the polymer ceramic precursor MK is used, the weight percentages of the casting solution include: 16wt% of anhydrous ethanol, 24wt% of DMF, 8wt% of PMMA, 34wt% of α-Al2O3 and 16wt% of MK.

Citation Information

Patent Citations

  • Method for preparing compact single-phase or complex-phase mullite ceramics through sintering at low temperature

    CN108484151A

  • Flexible polysiloxane fiber membrane and their preparation method and application thereof

    CN109868559A

  • Method for preparing mullite nanofiber by electrospun two-phase precursors

    CN110117841A

  • Preparation method of continuous ceramic fiber

    CN110863265A

  • Preparation method of flexible high-temperature-resistant SiO2 ceramic nanofiber membrane

    CN113668139A